2019
DOI: 10.5006/3192
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Induced Stress Cracking of Swaged Super Duplex Stainless Steel Subsea Components

Abstract: A recent subsea failure of two subsea connectors made of UNS S32760, a 25 wt% Cr super duplex stainless steel, led to an extensive root cause failure analysis. The components showed a single longitudinal crack along a swaged section, which arrested toward its thicker end. The brittle nature of the fracture surface, calcareous deposits on the component, and exposure to cathodic protection suggested hydrogeninduced stress cracking-a form of environmentally assisted cracking-as a plausible failure mechanism. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Grain boundaries in DSS may not be susceptible sites to crack formation since grain boundaries, particularly interphase boundaries, may act as strong trap sites for hydrogen, reducing the resistance to HE. Therefore, finely-grained microstructures typically outperform coarse ones, explained by trapping and elongated diffusion path due to a larger tortuosity (Woollin and Gregori, 2004;Chai et al, 2009;Bahrami and Woollin, 2010;Kivisäkk, 2010;Kivisäkk and Ciurea, 2011;Sofia Hazarabedian et al, 2019). Plastic deformation typically preludes crack formation, and therefore intensified deformation in the microstructure can be understood as the most incipient degradation stage in DSS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Grain boundaries in DSS may not be susceptible sites to crack formation since grain boundaries, particularly interphase boundaries, may act as strong trap sites for hydrogen, reducing the resistance to HE. Therefore, finely-grained microstructures typically outperform coarse ones, explained by trapping and elongated diffusion path due to a larger tortuosity (Woollin and Gregori, 2004;Chai et al, 2009;Bahrami and Woollin, 2010;Kivisäkk, 2010;Kivisäkk and Ciurea, 2011;Sofia Hazarabedian et al, 2019). Plastic deformation typically preludes crack formation, and therefore intensified deformation in the microstructure can be understood as the most incipient degradation stage in DSS.…”
Section: Resultsmentioning
confidence: 99%
“…The cracking of either phase in the duplex microstructure -not observed in this workwould imply the degradation of the other phase because the latter phase would have been insufficient in providing support against cracking. Typically, cracks initiate in ferrite grains in coarse duplex microstructures (>30 µm austenite spacing) (Byrne et al, 2016;Sofia Hazarabedian et al, 2019). The ferrite is thus considered as the more susceptible phase (Byrne et al, 2016;Sofia Hazarabedian et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all circumstances make the ferrite more prone to chloride-induced stress corrosion cracking. For example, Örnek found that the austenite in 2,205 duplex stainless steel suffers from chloride-induced stress corrosion cracking in the drop test [115] . .…”
Section: Chloride-induced Stress Corrosion Crackingmentioning
confidence: 99%
“…The effect of Cr 2 N precipitate and the resulting depletion of Cr and Mo, on the localised corrosion resistance of duplex stainless are relatively well established [91][92][93]. Cr 2 N precipitation in the welds has also been implicated in HE/HISC [94], where Cr depletion mechanism cannot account for the increased HE susceptibility. It is possible that coherent alpha prime precipitation that was not detected by these authors contributed to increased HE susceptibility.…”
Section: Effect Of Incoherent Precipitates (Carbides Nitrides and Int...mentioning
confidence: 99%